On the procedural risks of automation activities in general administrative proceedings (Discourse of Law and Administration, 2024)
Automation, understood as acting with the use of operating (ICT) systems without human intervention, is increasingly entering all areas of human life. This also applies to the relationship between an individual and the state represented by public administration bodies. The scope of regulation in this area is gradually broadening. In the initial period, the legislator introduced solutions based on the use of so-called new technologies both internally within the public administration and at the interface with the party. Currently, solutions for the implementation of adjudicatory actions against a party are becoming more and more widespread. After the occasional solutions adopted in the substantive legislation, developments to this effect have also appeared in the Code of Administrative Procedure. However, the mere introduction of the possibility to use automatically generated letters (Article 14 § 1b of the Code of Civil Procedure) is insufficient. The study analyses the compatibility of performing ‘automatic’ activities with other provisions of the Code of Civil Procedure and European Union law. In the conclusion, de lege ferenda proposals are presented which, in the author’s opinion, will make it possible to remove the existing inconsistencies so as to avoid a situation in which divergent interpretations of provisions will result in different positions of the addressees of decisions.
Keywords: principle of written form; administrative jurisdiction; automatically generated letters